indonesia Pengaruh Penanaman Modal Dalam Negeri (PMDN) dan Penanaman Modal Asing (PMA) Terhadap Peningkatan Produk Domestik Bruto di Indonesia - Nidya Lestari; Maya Panorama (Al-Buhuts, 2022)
The purpose of this study is to analyze the effect of investment on the increase in gross domestic product. This research is quantitative research based on secondary data sourced from the Central Statistics Agency and the Investment Coordinating Board. Data analysis used multiple linear regression. The results show that domestic investment and foreign investment basically increase gross domestic product, in this study domestic investment has a significant effect on gross domestic product, Similarly, foreign investment affects gross domestic product.